2004
DOI: 10.1111/j.1365-2621.2004.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition, antioxidants and lipid oxidation in chicken breasts from different production regimes

Abstract: Chicken breast from nine products and from the following production regimes: conventional (chilled and frozen), organic and free range, were analysed for fatty acid composition of total lipids, preventative and chain breaking antioxidant contents and lipid oxidation during 5 days of sub-ambient storage following purchase. Total lipids were extracted with an optimal amount of a cold chloroform methanol solvent. Lipid compositions varied, but there were differences between conventional and organic products in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 35 publications
5
19
1
10
Order By: Relevance
“…Although pasture intake was available for the birds in the organic system in this study between the ages of 21 and 81 days, the thigh meat of the organically reared birds was markedly lower in omega-3 content when compared with birds kept indoors. The report by Jahan et al (2004), that demonstrated that organic breast meat had a significantly lower contents of n-3 fatty acids, but a higher content of total PUFA, n-6 and n-6/n-3 ratios, is in full agreement with the present findings. Also, a recent study showed that free-range meat contained lower quantities of most n-3 fatty acids (C18:3, C18:4, EPA) and had a consistently higher n-6/n-3 ratio than that from intensively reared birds (Givens et al, 2011).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Although pasture intake was available for the birds in the organic system in this study between the ages of 21 and 81 days, the thigh meat of the organically reared birds was markedly lower in omega-3 content when compared with birds kept indoors. The report by Jahan et al (2004), that demonstrated that organic breast meat had a significantly lower contents of n-3 fatty acids, but a higher content of total PUFA, n-6 and n-6/n-3 ratios, is in full agreement with the present findings. Also, a recent study showed that free-range meat contained lower quantities of most n-3 fatty acids (C18:3, C18:4, EPA) and had a consistently higher n-6/n-3 ratio than that from intensively reared birds (Givens et al, 2011).…”
Section: Resultssupporting
confidence: 82%
“…The fatty acid composition in the meat shows varying responses in the different rearing systems. However, most studies indicated higher PUFA, n-3 and n-6 concentrations when birds were grown under organic and free range systems (Jahan et al, 2004;Grashorn & Serini, 2006;Husak et al, 2008;. The fatty acid composition of the chicken meat was also significantly influenced by the rearing system in the present study.…”
Section: Resultssupporting
confidence: 55%
“…The incidence of several common metabolic diseases associated with deficiencies of critical dietary minerals, vitamins, and amino acids can be reduced by consuming poultry products because they are rich in all essential nutrients (Cherian, Seena, Bullock, & Antony, 2005). Chicken meat products can be considered an important component in healthy diets (Jahan, Paterson, & Spickett, 2004), as they contain a higher proportion of polyunsaturated fatty acids compared with meat from other species (Berzaghi, Dalle Zotte, Jansson, & Andrighetto, 2005), high nutritional value, and distinct flavor (Patsias, Badeka, Savvaidis, & Kontominas, 2008). However, poultry meat products are perishable foods as they deteriorate within 4-10 days, even when stored at refrigeration temperature (Jimenez et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a relatively limited number of studies that have compared organic and conventional broiler meat quality (Castellini et al, 2002;Ristic, 2004;Jahan et al, 2004;Grashorn & Serini, 2006;Castellini et al, 2006;Husak et al, 2008;Martino et al, 2008), we have not found a sufficient number of studies that define the differences of cost between organic and conventional broiler production. The cost of broiler production can vary depending on many factors, such as final crop characteristics (the name of the brand and the quality of the product), feed price (basically, cereal prices), climate factors, and genetic lines employed (FAO/EBRD, 1999).…”
Section: Introductionmentioning
confidence: 66%